A soluble phosphorylated tau signature links tau, amyloid and the evolution of stages of dominantly inherited Alzheimer’s disease - Barthélemy, Nicolas R.; Li, Yan; Joseph-Mathurin, Nelly; Gordon, Brian A.; Hassenstab, Jason; Benzinger, Tammie. L. S.; Buckles, Virginia; Fagan, Anne M.; Perrin, Richard J.; Goate, Alison M.; Morris, John C.; Karch, Celeste M.; et al. (Nature Medicine, 2020)
Development of tau-based therapies for Alzheimer’s disease requires an understanding of the timing of disease-related changes in tau. We quantified the phosphorylation state at multiple sites of the tau protein in cerebrospinal fluid markers across four decades of disease progression in dominantly inherited Alzheimer’s disease. We identified a pattern of tau staging where site-specific phosphorylation changes occur at different periods of disease progression and follow distinct trajectories over time. These tau phosphorylation state changes are uniquely associated with structural, metabolic, neurodegenerative and clinical markers of disease, and some (p-tau217 and p-tau181) begin with the initial increases in aggregate amyloid-β as early as two decades before the development of aggregated tau pathology. Others (p-tau205 and t-tau) increase with atrophy and hypometabolism closer to symptom onset. These findings provide insights into the pathways linking tau, amyloid-β and neurodegeneration, and may facilitate clinical trials of tau-based treatments. Site-specific hyperphosphorylations of tau in the cerebrospinal fluid change with disease course, and correlate with pathology and cognitive decline in dominantly inherited Alzheimer’s disease.